Aberration correction for transcranial photoacoustic tomography of primates employing adjunct image data - Huang, Chao; Nie, Liming; Schoonover, Robert W; Guo, Zijian; Schirra, Carsten O; Anastasio, Mark A; Wang, Lihong V (Journal of Biomedical Optics, 2012)
A challenge in photoacoustic tomography (PAT) brain imaging is to compensate for aberrations in the measured photoacoustic data due to their propagation through the skull. By use of information regarding the skull morphology and composition obtained from adjunct x-ray computed tomography image data, we developed a subject-specific imaging model that accounts for such aberrations. A time-reversal-based reconstruction algorithm was employed with this model for image reconstruction. The image reconstruction methodology was evaluated in experimental studies involving phantoms and monkey heads. The results establish that our reconstruction methodology can effectively compensate for skull-induced acoustic aberrations and improve image fidelity in transcranial PAT.